The Compatibility of Autonomous Weapons with the Principles of International Humanitarian Law. (21st January 2022) - Winter, Elliot
Abstract: The emergence of autonomous weapons remains a hot topic in international humanitarian law. Much has been said by States, international organisations, non-governmental organisations and academics on the matter in recent years. However, no agreement has been reached on how best to regulate this nascent technology. In the absence of any such agreement, the best approach is to analyse autonomous weapons through the lens of the principles of international humanitarian law. After humanity and military necessity are debunked as false principles, this article tests the compatibility of autonomous weapons with distinction, proportionality and precaution. It argues that autonomous weapons are not currently able to comply with these principles, owing primarily to a lack of sufficiently advanced artificial intelligence and contextual awareness. However, it also argues that the path to international humanitarian law-compliant autonomous weapons is shorter, and more clearly defined, than many realise. Indeed, the article highlights various ways in which future technological advances could enable autonomous weapons to comply with the principles of international humanitarian law more rigorously than human beings. The article does not seek to address the compatibility of autonomous weapons with other aspects of international law or the morality of such weapons.